Efficient computational techniques for mistuning analysis of bladed discs: A review. (15th March 2017) - Yuan, Jie; Scarpa, Fabrizio; Allegri, Giuliano; Titurus, Branislav; Patsias, Sophoclis; Rajasekaran, Ramesh
Abstract: This paper describes a review of the relevant literature about mistuning problems in bladed disc systems, and their implications for the uncertainty propagation associated to the dynamics of aeroengine systems. An emphasis of the review is placed on the developments of the multi-scale computational techniques to increase the computational efficiency for the linear mistuning analysis, especially with the respect to the reduced order modeling techniques and uncertainty quantification methods. The non-linearity phenomena are not considered in this paper. The first two parts describe the fundamentals of the mechanics of tuned and mistuned bladed discs, followed by a review of critical research efforts performed on the development of reduced order rotor models. The focus of the fourth part is on the review of efficient simulation methods for the stochastic analysis of mistuned bladed disc systems. After that, we will finally provide a view of the current state of the art associated to efficient inversion methods for the stochastic analysis, followed by a summary. Highlights: Description of fundamental mechanisms of blades mistuning. Critical review of reduced order models to predict mistuning. Review of stochastic techniques for mistuning problems. One hundred thirty eight references cited and commented.